2015
DOI: 10.4172/2167-0501.1000e175
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on π-π Stackings and π-Cations in Prion Protein Structures

Abstract: π-π stackings and π-cations clearly do some contributions to maintain the structural stability of a normal cellular prion protein (PrP). This short article is to do a survey on the π-π stackings and π-cations in all the PrP structures listed in the PDB (www.rcsb.org) Bank. We find the following important π-π stackings: Y218-F175-Y169 (around the β2-α2 loop), Y162-Y128 (linking the two β-strands), F141-Y150-Y157 (in α-helix 1), H187-F198 (linking α-helix 2 and the α2-α3 loop); and we also find the following imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…At the same time we found other important π-π stackings such as F175-Y218 and π-cations such as F141-R208, F198-R156, and H155-R136 (Table 4). We can see around the β2-α2 loop there is a "π-chain/circle" Y128-F175-Y218-Y163-F175-Y169-R164-Y128(-Y162) as reported in (Zhang, 2015a(Zhang, & 2015b (where another "π-chain" R208-Y141-Y150-Y157-F198-H187 covering H1 is also reported). By the way, we found the "Cα-distance" to calculate π-cations of George Priya Doss et al ( 2013) is not a perfect way for calculations (Table 4).…”
Section: Bufprp Is Stable Under Neutral-or Low-ph Environments At Roo...supporting
confidence: 60%
“…At the same time we found other important π-π stackings such as F175-Y218 and π-cations such as F141-R208, F198-R156, and H155-R136 (Table 4). We can see around the β2-α2 loop there is a "π-chain/circle" Y128-F175-Y218-Y163-F175-Y169-R164-Y128(-Y162) as reported in (Zhang, 2015a(Zhang, & 2015b (where another "π-chain" R208-Y141-Y150-Y157-F198-H187 covering H1 is also reported). By the way, we found the "Cα-distance" to calculate π-cations of George Priya Doss et al ( 2013) is not a perfect way for calculations (Table 4).…”
Section: Bufprp Is Stable Under Neutral-or Low-ph Environments At Roo...supporting
confidence: 60%
“…5, we may know at S2-H2 loop and its contacts with the C-terminal end of H3 there are the following ππ-stacks Y169-F175, F175-Y218, Y163-Y218, and the following π-cations R164-Y169, R164-Y128, which clearly contribute to the clearly and highly ordered S2-H2 loop structures [65]. For buffaloPrP, we found another two π-stackings: Y163-F175-Y128 [65,66]. Thus, for PrPs, we found an interesting "π-circle" Y128-F175-Y218-Y163-F175-Y169-R164-Y128(-Y162) around the S2-H2 loop.…”
Section: The Hybrid Idea and Some Hybrid Optimization Methodsmentioning
confidence: 99%
“…Hence, it appears that misfolding can potentially commence from either of the two isoenergetic but structurally distinct sub-populations, PUF2* and PUF2**. Mutation of the conserved Pro residues (Zhang, 2015) affects the stability of PUF2*, while mutation of the conserved aromatic residues affects the stability of PUF2** (Figure S5). In this way, misfolding of different mutant variants may commence from or proceed via either PUF2* or PUF2**.…”
Section: Misfolding Can Potentially Commence From Multiple Pufsmentioning
confidence: 99%
“…Tyr168 and Tyr217 are strictly conserved, whereas Phe174 is conserved in all but two species (Huang & Caflisch, 2015). The aromatic interactions between Tyr168, Phe174, and Tyr217 are the most conserved aromatic interactions observed in the structures of different mammalian prion proteins (Zhang, 2015). MD simulation studies have suggested that favorable interactions between Tyr168, Phe174, and Tyr217 stabilize the interface of the β2‐α2 loop and the C‐terminal end of α3 (Huang & Caflisch, 2015; Jung Cheng & Daggett, 2014).…”
Section: Introductionmentioning
confidence: 99%